Implementsi Kode Etik Profesi Polri di Polresta Gorontalo Kota - Andik Gunawan; Yanti Aneta; Dwi Indah Yuliani Solihin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the implementation of the Police Professional Code of Ethics at Gorontalo City Police Resort (Polresta Gorontalo Kota) as a framework for strengthening integrity, accountability, and professionalism within the Indonesian National Police. Although the Code of Ethics has been formally institutionalized as a guiding principle for behavior, its implementation remains challenged by discrepancies between written norms and field practices. Several critical issues were identified, including the suboptimal internalization of ethical values, limited supervisory capacity of the Professional and Security Division (Propam) due to workload constraints, and inconsistencies in the imposition of sanctions for similar violations. On the other hand, leadership commitment to professionalism, an organizational culture oriented toward integrity, and the adoption of digital-based public service innovations were found to be supporting factors in advancing ethical enforcement. This research employed a qualitative descriptive approach through interviews, documentation, and observation, with analysis conducted using thematic categorization supported by relevant theories of professional ethics and organizational behavior. The findings confirm that the success of code of ethics implementation is largely determined by the clarity of regulations, the capacity of implementing personnel, the consistency of sanction enforcement, and community involvement in oversight processes. The results support the hypothesis that consistent and effective implementation of the professional code of ethics significantly enhances both the professionalism of police officers and public trust. This study contributes to the broader discourse on professional ethics in policing and highlights the importance of integrating regulatory, organizational, and social dimensions in sustaining ethical conduct within law enforcement institutions.